Text and Its Context: The Critical Discourse Analysis of the Third Development Plan of Iran (1962-1967) According to Baldwin’s Monography - Hojatolloh Rahimi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Although interest in the discourse analysis of national development policies and plans has been growing in recent years; however, little attention has been paid to the context in which these texts are articulated. This article, by supposing essential relationships between text and its context, aimed to interpret the third development plan of Iran and to analyze the social context of the plan according to Baldwin’s monography and the method of the Critical Discourse Analysis (CDA). The article identified “the order of discourse of planning and development” as a joint around which two dominant discourses including (i) “individually centralized planning discourse” and (ii) “growth-based development discourse” are articulated. In addition, “a participatory decentralized planning discourse” and “a distribution-based development discourse” have been identified as competing discourses in relation to the first two discourses. Finally, the article by analyzing the political and cultural context of the plan showed that the production of the plan as a text, instead of following a rational-scientific process, has mainly been influenced by ideological-discursive formulations seeking to maintain specific relation of power among key actors and geographical spaces through text.